Development and transferability of microsatellite markers for species of the saltans group of Drosophila (Diptera: Drosophilidae) - Roman, B. E. [UNESP]; Trava, B. M. [UNESP]; Madi-Ravazzi, L. [UNESP] (Funpec-editora, 2020)
Microsatellite markers, also known as single sequence repeats (SSRs), are highly polymorphic, fast evolving, and regarded as neutral markers. Due to these traits, they have been widely used in population studies. The development of SSRs for a given species opens possibilities for their application in population studies of other species that are phylogenetically related. We tested 16 primer pairs developed for Drosophila sturtevanti and the transferability test of them in 14 species of the saltans group of Drosophila. The optimal amplification conditions were established using the DNA of 15 D. sturtevanti males. Among the primers pairs developed, 13 have successful in the amplification for D. sturtevanti. And in the transferability test, the total percentage of transfer was nearly 50%. The species with the highest success rates of heterologous amplification were in the sturtevanti subgroup. Two microsatellite markers amplified in all the species, while one would not amplify for any of the saltans group species. These data demonstrate the usefulness of testing transferability of genetic markers, which may be used in studies of genetic diversity and population structure of D. sturtevanti and other species of the saltans group of Drosophila.
Keywords: Genetic diversity; Genomic library; Molecular markers; Neutral markers; SSR